The perfectionists : how precision engineers created the modern world - Winchester, Simon (Harper, an imprint of HarperCollins Publishers, 2018)
"The revered New York Times bestselling author traces the development of technology from the Industrial Age to the Digital Age to explore the single component crucial to advancement--precision--in a superb history that is both an homage and a warning for our future." -- Amazon.